Implementation of Playout Algorithm to Streaming Media File for Reducing Packet Loss Over Internet Protocol - Kasman Kasman; Shung Ping Chen; Johannes Gerdes; Mochamad Hariadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2010)
PlayOut Algorithm has considerable contributed to the interactive communication over Internet like voice communication and VoIP. Some papers have, including playout adaptive Algorithm, investigated how to reduce and minimize the effect of Jitter which are much constitute to the packet loss. In streaming media file using H.323 format for video has been investigated in this paper. By using Network Analyzer for various network condition has represented network behaviour over the network VLAN. The use of playout Algorithm to estimate the buffering delay time for scheduling each packet arrived in receiver has remained the reduction of packet loss under 5% for traffic load utilization generator up to 21% using Network Analyzer.